GAMBARAN TINGKAT PENGETAHUAN MAHASISWA KEPERAWATAN UNIVERSITAS RIAU TENTANG PENCEGAHAN COVID-19 - Elsa Aulia Rizal; Darwin Karim; Rismadefi Woferst (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2021)
Introduction: Covid-19 is a disease caused by a new corona virus called sars-cov-2 that causes respiratory infections, ranging from the common cold to serious illness. With good knowledge of the covid-19 prevention, it will help governments to suppress the prevalence. Preventive measures can be made to break links by applying health protocols such as wearing a mask, washing your hands with soap or handsanitizer, applying social distension, physical fishing, and so on. The study was intended to identify the level of knowledge the student Faculty of Nursing at the University of Riau on the prevention of Covid-19. Method: The study used a quantitative descriptive research design. The research sample is 133 new students of a 2020 program derived from the criteria of inclusion, using a total sampling technique. The data analysis used is univariate. Results: 119 student respondents (89.5%) have a good knowledge of Covid-19 prevention, and 14 student respondents (105%) have enough knowledge about Covid-19 prevention. Conclusion: Judging by the level of nursing students at the University of Riau, dominant in their knowledge of Covid-19 prevention, it is expected that this study will add some information on how Covid-19 prevention inan effort to minimize Covid-19 infection rates in communities, especially nursing students at the University of Riau.Keywords: Covid-19 prevention, Knowledge level, Nursing student